2017
DOI: 10.1080/14767058.2017.1312328
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the helicobacter pylori seropositivity with systemic and local oxidative status and hyperemesis gravidarum: a pilot study

Abstract: Our results suggest that significantly increased oxidative burden and slightly decreased antioxidative capacity of saliva may be involved in the pathogenesis of HG and this condition may be the result of HP infection which was found to be significantly more common in women with poor oral hygiene and HG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…The authors suggested that the increased oxidative burden of saliva may be involved in the development of HG and may be the result of H. pylori infection. 63 In a study by Di Simone et al, pre-eclamptic women were shown to have a higher seroprevalence of H. pylori infection and CagA positivity compared to controls. H. pylori infection was also associated with abnormal uterine artery flow and H. pylori-positive IgG fractions were able to bind trophoblast and endometrial cells in vitro, thus inhibiting angiogenesis.…”
Section: Obs Te Tri C Smentioning
confidence: 97%
See 1 more Smart Citation
“…The authors suggested that the increased oxidative burden of saliva may be involved in the development of HG and may be the result of H. pylori infection. 63 In a study by Di Simone et al, pre-eclamptic women were shown to have a higher seroprevalence of H. pylori infection and CagA positivity compared to controls. H. pylori infection was also associated with abnormal uterine artery flow and H. pylori-positive IgG fractions were able to bind trophoblast and endometrial cells in vitro, thus inhibiting angiogenesis.…”
Section: Obs Te Tri C Smentioning
confidence: 97%
“…A case‐control study from Turkey including 50 pregnant women showed that those with hyperemesis gravidarum (HG) had a higher oxidative burden in their saliva and that H. pylori seropositivity was six times higher than in the control group. The authors suggested that the increased oxidative burden of saliva may be involved in the development of HG and may be the result of H. pylori infection …”
Section: Obstetricsmentioning
confidence: 99%
“…Beyazit et al reported that HG is an oxidative stress condition, regardless of H. Pylori infection, based on women with pregnancies complicated by HG ( n = 33), pregnant women without HG ( n = 30), and healthy non-pregnant women ( n = 31) ( 92 ). However, in 2018, Goymen et al showed that HG may lead to a significantly increased oxidative burden and slightly decreased antioxidative capacity of saliva, which may be the result of H pylori infection and that such infection was more common in women with poor oral hygiene and HG ( 93 ).…”
Section: Pathogenesismentioning
confidence: 99%
“…H. pylori ‐positive women (n=2363, 42.6%) were more likely to report daily vomiting (OR: 1.44; 1.16‐1.78). A Turkish study suggested surprisingly that significant increased oxidative burden and slightly decreased antioxidative capacity of saliva may be involved in the pathogenesis of hyperemesis gravidarum and this condition may be the result of H. pylori infection (seropositivity 24% vs 4% of controls) in women with poor oral hygiene …”
Section: Miscellaneousmentioning
confidence: 99%